A performance comparison of oversampling methods for data generation in imbalanced learning tasks - Dattagupta, Samrat Jayanta (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research e CRM